Conserved MicroRNAs in Human Nasopharynx Tissue Samples from Swabs Are Differentially Expressed in Response to SARS-CoV-2 - Eichmeier, Ales; Kiss, Tomas; Kocanova, Maria; Hakalova, Eliska; Spetik, Milan; Cechova, Jana; Tichy, Boris (Genes, 2022)
The use of high-throughput small RNA sequencing is well established as a technique to unveil the miRNAs in various tissues. The miRNA profiles are different between infected and non-infected tissues. We compare the SARS-CoV-2 positive and SARS-CoV-2 negative RNA samples extracted from human nasopharynx tissue samples to show different miRNA profiles. We explored differentially expressed miRNAs in response to SARS-CoV-2 in the RNA extracted from nasopharynx tissues of 10 SARS-CoV-2-positive and 10 SARS-CoV-2-negative patients. miRNAs were identified by small RNA sequencing, and the expression levels of selected miRNAs were validated by real-time RT-PCR. We identified 943 conserved miRNAs, likely generated through posttranscriptional modifications. The identified miRNAs were expressed in both RNA groups, NegS and PosS: miR-148a, miR-21, miR-34c, miR-34b, and miR-342. The most differentially expressed miRNA was miR-21, which is likely closely linked to the presence of SARS-CoV-2 in nasopharynx tissues. Our results contribute to further understanding the role of miRNAs in SARS-CoV-2 pathogenesis, which may be crucial for understanding disease symptom development in humans.
Keywords: Up-Regulation; Nasopharynx; analýza hlavních komponent; Real-Time Polymerase Chain Reaction; sekvenční analýza RNA; upregulace; SARS-CoV-2; mir-21; transkriptom; mikro RNA; down regulace; COVID-19; real-time RT-PCR; RNA, Viral; miRNAs; small RNA sequencing; Transcriptome; MicroRNAs; Down-Regulation; kvantitativní polymerázová řetězová reakce; Sequence Analysis, RNA; Principal Component Analysis; nazofarynx; Humans; High-Throughput Nucleotide Sequencing; vysoce účinné nukleotidové sekvenování; RNA virová; lidé